Alybayeva R.А., Kruzhayeva V., Abdrazakova G., Atabayeva S., Asrandina S. Investigation of the inﬂuence of genotypic factors on the accumulation of heavy metals by wheat: Al-Farabi Kazakh National University, UNESCO Chair in Sustainable Development, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
The most acute problem, solution of which has practical significance, is the contamination of agrocenoses by heavy metals near large industrial centers. It is necessary to develop agricultural systemsthat guarantee sustainable functioning of agricultural production, reduce the level of contamination ofproduced products by HM and by other chemical toxicants. The most promising direction in this areais the identification of plant objects characterized by a minimum accumulation of heavy metals. In thisregard, the purpose of our study was the identification of wheat forms resistant to priority pollutants inEast-Kazakhstan industrial region (zinc, cadmium, lead and copper).The objects of the study are different genotypes of winter and spring bread wheat. The plants were grown on the scientific test site in theconditions of natural pollution of environment, in the suburban zone of Ust-Kamenogorsk. The contentof heavy metals in plants end soil was determined by atomic absorption method. The experiments anddetermination of physiological parameters were carried out by the method of field experiment.The studyof heavy metals content in the root zone of wheat plants showed that plants experience stress from polymetallic soil contamination. Investigation of the accumulation of heavy metals in the organs of wheatshowed that winter and spring wheat differ in the distribution of heavy metals in the organs. In case ofwinter wheat, zinc and cadmium, in contrast to copper and lead, are actively supplied to the reproductive organs. In the case of spring wheat, zinc and cadmium accumulate in seeds in small quantities, andcopper and lead are significant in quantity and its content exceeds the MPC in almost all varieties. Largegenotypic differences were revealed in the accumulation of zinc, copper, cadmium and lead in plantorgans. According to the results of study, wheat varieties that accumulate less heavy metals are recommended for further use in breeding for resistance to metals.Key words: heavy metals, wheat, accumulation of metals, promising genotypes.